Respostas da cultura do tomate para processamento industrial a fatores ambientais e irrigação - Knapp, Fábio Miguel (2023)
The tomato crop for industry is strongly conditioned by environmental conditions. In this way, this work aimed to determine the meteorological variable with the greatest influence and contribution to growth and the thermal sum accumulated in each stage of development of different hybrids, in addition to evaluating the responses of tomato plants in two irrigation systems: central pivot sprinkler and located by subsurface drip. For this, experiments were set up in Abadia de Goiás, Hidrolândia, Itaberaí, Palmeiras de Goiás, Piracanjuba and Silvânia during the 2020 harvest, fortnightly collections of plants were carried out for biometric measurement of number of leaves, leaf area, number of branches, number of fruit and plant height, as well as the collection of meteorological variables from each location with the aid of an automatic meteorological station, to determine the variable with the greatest interference in the growth and development of the crop, canonical correlation and multivariate Stepwise regression were used, in addition to separation of averages by Scott-knott. The main variable that affected crop growth was water availability. The water supply was responsible for 86.2% of the plant height and 79.6% of the leaf area index. On the other hand, the average air temperature, solar radiation and accumulated thermal sum showed little influence on crop growth. The industrial tomato responded to the accumulated degree days, with the average degree days accumulated in the first and second seasons of 1,394 and 1,364 degree days, respectively, and its average cycle of 124 and 116 days from transplanting to maturation. The irrigation systems did not show savings in the amount of water used in the crop during the cycle, but the subsurface drip irrigation system provided a shorter period of leaf wetness, improving plant health, delaying senescence and leaf abscission and providing greater productivity and increase in water use efficiency in this system.